2008
DOI: 10.1063/1.2968611
|View full text |Cite
|
Sign up to set email alerts
|

Shock-tube study of relaxation in HCN

Abstract: Thermal vibrational relaxation in HCN mixtures with Kr has been observed with the laser-schlieren technique. The experiments cover the temperatures 750-2900 K and a large pressure range of 13-420 Torr in 5% and 20% HCNKr mixtures. Relaxation is extremely fast but appears to occur in two well-separated stages that are assigned to the vibrational transitions (000)-->(010) and (000)-->(100) with perhaps some lesser contribution from (000)-->(001). This interpretation is strongly supported by a comparison of net d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…About the collisional processes (see Table 4), process 1 represents the collisional de-excitation of the HCN ν 2 levels in collisions with the major atmospheric constituent in Titan atmosphere, N 2 . The rate coefficient has been taken from the recent measurements of Srinivasan et al (2008) for collisions with Kr, scaled by a factor of 0.3 to account for the k 2 (N 2 )/k 2 (Kr) ratio, as reported by Arnold and Smith (1981).…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…About the collisional processes (see Table 4), process 1 represents the collisional de-excitation of the HCN ν 2 levels in collisions with the major atmospheric constituent in Titan atmosphere, N 2 . The rate coefficient has been taken from the recent measurements of Srinivasan et al (2008) for collisions with Kr, scaled by a factor of 0.3 to account for the k 2 (N 2 )/k 2 (Kr) ratio, as reported by Arnold and Smith (1981).…”
Section: The Modelmentioning
confidence: 99%
“…The relaxation of one ν 1 quanta has enough energy to excite up to three ν 2 vibrations. The rate for this process has also been taken from Srinivasan et al (2008) and corrected for the k 2 (N 2 )/k 2 (Kr) ratio as reported by Arnold and Smith (1981).…”
Section: The Modelmentioning
confidence: 99%
“…The recent improvements and developments in diamond cell and shock-tube high-pressure apparatuses as well as the laser heating systems have opened up the possibility of observing 4 Present address: Correlated Electron Research Group, Advanced Science Institute (RIKEN), 2-1 Hirosawa, Wako, Saitama 351-0198, Japan. novel phase transitions for materials under high pressure and high temperature [1][2][3][4][5][6]. Similarly, there has been a substantial theoretical boost in the realistic modeling of materials under high pressure and temperature using various quantum mechanical approaches and algorithms [7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The present experiments cannot distinguish between the two possible paths, either the direct "triple" dissociation (1) or the two-step process through a dimer (2), but entropy considerations and the low binding energies calculated for likely dimers [45][46][47] would favor the direct path (1). A small contribution to the density gradient from HCN isomerization may occur at the highest temperatures, but the absence of such effect in direct HCN experiments [48] and the need for an unreasonably large rate here would seem to rule this out. The best agreement between RRKM calculations and experiment is with a barrier of 81 kcal/mol as was suggested in the calculations of Pai et al [13] and Dyakov et al [15], with a rather routine E down = 126(T /298) 0.9 .…”
Section: Discussionmentioning
confidence: 92%
“…In fact, a slightly better fit to these experiments can be achieved at the highest temperatures by including an estimated (see the Appendix) rate for the HCN isomerization as shown in Fig. 9, but our recent study of HCN itself [48] showed no indication of isomerization, so this seems quite unlikely. Perhaps the HCN is somehow formed with close to equilibrium HNC [11].…”
Section: Dissociationmentioning
confidence: 89%